Mineralocorticoid Receptor Antagonist Treatment for Steroid-Induced Central Serous Chorioretinopathy Patients with Continuous Systemic Steroid Treatment - Jin Young Kim; Ju Byung Chae; Jisoo Kim; Dong Yoon Kim (Journal of Ophthalmology)
Purpose. To investigate the effectiveness of mineralocorticoid receptor (MR) antagonist in patients with steroid-induced central serous chorioretinopathy (CSC). Methods. A retrospective review was conducted of steroid-induced CSC patients who were treated with the MR antagonist spironolactone 50 mg once per day for at least 1 month. The primary outcome measure was complete resolution rate of subretinal fluid (SRF) after spironolactone treatment. Secondary outcomes included central subfield thickness (CST), subfoveal choroidal thickness (SFCT), and best-corrected visual acuity (BCVA) changes after spironolactone treatment. Results. Seventeen eyes from 15 patients were included in this study. Conditions warranting chronic systemic steroid use were myasthenia gravis (6/15, 40%), glomerulonephritis (5/15, 33.3%), and organ transplantation (4/15, 26.7%). Mean symptom duration of CSC was 4.00 ± 3.04 months. After spironolactone treatment, 14 eyes (82.4%) showed complete resolution of SRF (P<0.001) without discontinuation of systemic steroid. CST and BCVA were significantly improved after spironolactone treatment. SFCT was significantly decreased after spironolactone treatment. No patients experienced electrolyte imbalance after spironolactone treatment. Conclusion. MR antagonist treatment may be a therapeutic option for steroid-induced CSC patients. This treatment modality may be especially beneficial for steroid-induced CSC patients who cannot discontinue steroid medication due to systemic conditions.